Kinetic and thermodynamic study of composite with jute fiber as reinforcement - Edja Florentin Assanvo; Kicoun Jean-Yves N’Zi Toure; Kanga Marius N’Gatta; David Boa (Center of Biomass & Renewable Energy, Diponegoro University, 2024)
In the present work, engineered by compression molding process via a hydraulic press, the A and B composite samples were carried out with 5% and 10% ratio respectively of Ricinodendron heudelotii oil-based alkyd resin in bio-based matrix made of unsaturated polyester using jute fibers as reinforcement material. The samples’ thermal decomposition was performed through thermogravimetry (TG) and derivative thermogravimetry (DTG) analyses. Both composite samples exhibit two stages of decomposition, where the main occurs at 200 - 550°C. Aiming to study and being able to model the thermal degradation of the elaborated composites, finding the kinetic triplets appears the best option to describe the kinetic process undergo by the composites in order to evaluate the performance application of the composites. Two non-isothermal techniques, Flynn-Wall-Ozawa (FWO) and Kissinger have been used to assess the activation energy Ea, and it is found that the apparent activation energy varies with the degree of conversion indicating that both composites decompose with a multiple step mechanism process. The appropriate reaction model for the second stage of decomposition was best suited with Johnson-Mel-Avrami (n<1) model and has been established, allowing us to model thermal degradation behavior of our elaborated composite material and set predictions. The estimated Arrhenius factor values were respectively about A and B composites, 4.12.1015 min-1 and 10.42.1015 min-1, allowing us to set the final equation characterizing the degradation process for the second and main decomposition stage. Finally, as a result of comparison between A and B composites, A appears to be the more thermally stable due to its lower values of Arrhenius pre-exponential factor over the main stage of decomposition and higher calculated the activation energy values.